Answer:
Explanation:
Polynomial:
p(x) = ax³ + bx + x
Let g(x) = x² + kx + 1 .
g(x) is a factor of p(x). So, p(x) is divided by g(x), the remainder will be 0.
Divide p(x) by g(x) using long division method. {attached as an image}.
By doing long division, we get the remainder.
Remainder = bx - ax + k²ax + ka + c
= (b - a + k²a)x+ [ka + c]
Remainder = 0
b - a + k²a = 0 and ka + c = 0
ka + c = 0
ka = -c
k = -c/a ----------------(I)
b - a + k²a = 0
![\sf b -a + (c^2)/(a^2)*a=0 -------[From \ (I)]\\\\b - a + (c^2)/(a)=0\\\\Multiply \ the \ above \ equation\ by \ a \\\\ab - a^2 + c^2 = 0\\\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/zez8xqabg8ifsep7upm5pk3bulmf5hy8jf.png)
ab = a² - c²
Hence, proved.